Correlation between the burden of family caregivers and health status of people with diabetes mellitus - Niko Dima Kristianingrum; Dian Azizah Ramadhani; Yati Sri Hayati; Setyoadi Setyoadi (SAGE Publishing, 2021)
Background: Family caregivers play an important role in providing long-term care for people with diabetes mellitus because it is a chronic disease that requires critical attention. This increases the burden of family caregivers which affects the health status of people with this disease. Therefore, the aim of this study is to determine the correlation between the burden of family caregivers and the health status of people with diabetes mellitus.  Design and methods: This is an analytic observational study which was carried out in the work area ofpublic health centers in Malang City using a cross-sectional design approach. The subjects used were 327 people with diabetes mellitus and their families were selected using the cluster sampling technique. Data collection was carried out using demographic data instruments, Zarit Burden Interview (ZBI) questionnaire to measure the burden of family caregivers and the SF 12 questionnaire to measure the health status of people with diabetes mellitus. Results: The results of the Spermank-Rank statistical test showed that there was a negative relationship between the burden of family caregivers and the health status of people with diabetes mellitus (p-value 0.000 and coefficient value of -0.333). Conclusions: It was concluded that the lesser the burden on family caregivers, the better the health status of people with diabetes mellitus. Therefore, interventions are needed to reduce the burden of family caregiver and improve the health status of patients with diabetes mellitus.